Teachers perceptions about supporting youth participation in schools: Experiences from schools in England, Italy and Lithuania. (July 2019) - Leek, Joanna
The understanding of youth participation in the current article relates to ideas of citizenship and active involvement in global concerns. In this understanding of the term, schools are important agents for education for global citizenship, and play a role in the developing engagement of young people. Using data from focus groups with teachers ( n  = 45) from secondary schools in England, Italy and Lithuania, the current research seeks to extend discussion of youth participation by identifying distinctive features of participation of students at the school level. Although research into youth civic participation is rapidly growing, this topic remains partially unexplored, particularly in relation to school settings, opportunities and benefits of developing students' civic participation in schools. Findings are important for policy makers and teachers who attempt to promote civic participation in schools among students. The analysis shows that teachers' concepts of youth participation are grounded in their cultural context, and teachers' activities are undertaken intuitively. Analysis of teachers' interviews led to the identification of four common overarching themes that relate to the significance of education policy, school leadership, teacher training, and youth–adult partnerships, all in the context of youth participation.